Participations - Mariekie Burger (Communicare)
Currently the dominant form of universities development oriented community engagement is based on an institutional project-based theoretical framework. This framework has been criticised in the scholarly discipline of Development Communication and Social Change for being diffusion-based in nature, for its rigid linearity and subsequent hierarchically unequal power relationships, and for its uncritical validation of a particular form of knowledge. Against the background of this critique, paired with the current pronounced global awareness regarding the role of public universities in society, this conceptual article critically investigates a range of options for development-oriented community engagement by South African public universities. These options are based on different theoretical frameworks that already exist in the field of Development Communication and Social Change, namely: modernisation; dependency disassociation and social movements; Freirean dialogical pedagogy; UNESCO’s media system approach (that foregrounds access, participation and self-management); and participatory communication for development and social change. In so doing, the article suggests that universities should critically consider the following aspects when embarking on development-oriented community engagement: 1) evaluate the main assumptions of the framework, 2) consider the complex interplay between internal and external factors that cause problems of development, 3) consider the epistemology of knowledge, 4) reflect on the purpose and nature of community participation, and 5) consider aspects related to expressions of voice and identity in the public sphere instead of focusing only on measurable and material aspects as outcomes.